2020
DOI: 10.1101/2020.06.30.178640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Cell Protein Atlas of Transcription Factors Reveals the Combinatorial Code for Spatiotemporal Patterning theC. elegansEmbryo

Abstract: SUMMARYA high-resolution protein atlas is essential for understanding the molecular basis of biological processes. Using protein-fusion reporters and imaging-based single-cell analyses, we present a protein expression atlas of C. elegans embryogenesis encompassing 266 transcription factors (TFs) in nearly all (90%) lineage-resolved cells. Single-cell analysis reveals a combinatorial code and cascade that elucidate the regulatory hierarchy between a la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…Finally, while elt-1 has a well-defined known role in epidermal fate specification(57), our work shows that it is also required for nob-1 enhancer activity. This is consistent with other recent work identifying defects in cell division patterns and the expression of the neurogenic TF lin-32 in elt-1 mutants(58). The ability of developmental transcription factors to “moonlight’ is likely facilitated by complex regulation by multiple enhancers as seen for nob-1/php-3 , and ceh- 13 (30, 31) since enhancer evolution can enable genes to be expressed at different locations and times in development(59, 60).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, while elt-1 has a well-defined known role in epidermal fate specification(57), our work shows that it is also required for nob-1 enhancer activity. This is consistent with other recent work identifying defects in cell division patterns and the expression of the neurogenic TF lin-32 in elt-1 mutants(58). The ability of developmental transcription factors to “moonlight’ is likely facilitated by complex regulation by multiple enhancers as seen for nob-1/php-3 , and ceh- 13 (30, 31) since enhancer evolution can enable genes to be expressed at different locations and times in development(59, 60).…”
Section: Discussionsupporting
confidence: 93%
“…An intriguing question is when and how equivalent chromatin activity landscape is precisely specified in early progenitor cells that are not lineage-related. Since progenitor cells from different cell lineages generally exhibit divergent chromatin activity and gene expression programs (Packer et al, 2019;Ma et al, 2020), the specification of equivalent chromatin activity would be a regulated process. In rare cases, L-R symmetric cells exhibit functional asymmetry (Hobert, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given that cells of a tissue derive from different lineages, we tested whether lineage origin accounts for this intra-tissue chromatin heterogeneity. Our recent finding using cellular protein expression of transcription factors has revealed that many tissue-specific TFs show lineagerestricted expression, contributing to a lineage-dependent intratissue heterogeneity in gene expression (Ma et al, 2020). Here, we further tested whether chromatin changes underlie this pattern.…”
Section: Tissue-based Convergence Of Cellular Chromatin Activity Landscape Upon Differentiationmentioning
confidence: 92%
See 1 more Smart Citation